Epidemiology of mouldy core and core rot of apple in Himachal Pradesh, India - DHARMESH GUPTA, HANS RAJ*, J. N. SHARMA and (Indian Phytopathology, 2017)
Mouldy core and core rot of apple caused by Alternaria alternata has emerged an economically important disease in Himachal Pradesh, India causing direct losses to the growers. The fungus remains dormant inside the calyx of the fruit and later becomes active when the starch content of the fruits get converted into sugar and hence causes the post harvest disease, where the rotting of the fruits starts from the core region. In vitro studies on the effect of temperature and relative humidity on the growth of the conidia of Alternaria alternata causing mouldy core and core rot of apple revealed that, the temperature of 30Â°C and 100 per cent relative humidity were optimal for conidial germination. Among different weather parameters, cumulative rainfall was directly correlated with disease development. Regression analysis further showed that 91.00 per cent variation in pre-harvest fruit drop was due to mouldy core and core rot. Medium sized Starking Delicious apple fruits with open sinus/calyx tube and length: width ratio falling in 0.96 to 1.05 mm showed maximum incidence of mouldy core and core rot in the field.